Lithium Lanthanum Zirconium Oxide (LLZO) Powder

Microwave plasma treatment of LLZO powders produces spherical particles with narrow size distributions, addressing the issues of conventional methods by enhancing sintering and conductivity for solid state batteries.

JP7607586B2Active Publication Date: 2024-12-276K INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2021564472
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-30
Filing Date
2020-04-29
Publication Date
2024-12-27
Estimated Expiration
2040-04-29

AI Technical Summary

Technical Problem

Conventional methods for producing lithium lanthanum zirconium oxide (LLZO) powders result in wide particle size distributions, irregular shapes, and poor material packing, leading to poor performance in solid state batteries due to low sintering driving forces and high residual porosity.

Method used

The production of LLZO powders using microwave plasma treatment, which produces spherical particles with a narrow particle size distribution and controlled stoichiometry, enabling high-density sintering and improved ionic conductivity.

Benefits of technology

The method results in LLZO powders with enhanced sintering properties, reduced porosity, and improved ionic conductivity, suitable for high-performance solid state battery components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607586000003
    Figure 0007607586000003
  • Figure 0007607586000004
    Figure 0007607586000004
  • Figure 0007607586000005
    Figure 0007607586000005
Patent Text Reader

Abstract

Disclosed herein are embodiments of doped and undoped spherical or ellipsoidal lithium lanthanum zirconium oxide (LLZO) powder products and methods of fabrication using microwave plasma techniques that can be incorporated into solid-state lithium-ion batteries. Advantageously, embodiments of the disclosed LLZO powders exhibit high quality, high purity stoichiometric composition, small particle size, narrow particle size distribution, spherical morphology, and customizable crystal structure.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Technology This application claims priority to U.S. Provisional Patent Application No. 62 / 841,039, filed April 30, 2019, and entitled "Lithium Lanthanum Zirconium Oxide (LLZO) Powder," the contents of which are incorporated herein by reference in their entirety.

[0002] Technical Field The present disclosure is generally directed, in some embodiments, to doped and undoped spherical or ellipsoidal lithium lanthanum zirconium oxide (LLZO) powder products and methods for making same. Summary of the Invention

[0003] Disclosed herein are embodiments of high quality, high purity stoichiometric LLZO powders having small particle size, narrow particle size distribution, and spherical morphology, as well as methods of making such powders. In some embodiments, the LLZO powders can include LLZO particles; the LLZO particles have a D50 of about 20 nm to about 500 nm, a D10 of D50÷4 or greater, and a D90 of D50×4 or less; and a sphericity factor of greater than about 0.6. ) and the structure of the LLZO particles is a crystalline garnet structure and / or an amorphous structure.

[0004] In some embodiments, D10 may be approximately equal to D50÷2. In some embodiments, D90 may be approximately equal to D50×2. In some embodiments, D50 may be from about 50 nm to about 500 nm. In some embodiments, D50 may be from about 100 nm to about 400 nm. In some embodiments, D50 may be from about 150 nm to about 300 nm. In some embodiments, D50 may be approximately equal to 200 nm.

[0005] In some embodiments, the LLZO particles include Li 7-3x M1x La 3 Zr 2 O 12 In some embodiments, the LLZO particles have a stoichiometric composition of Li 7-y La 3 Zr 2-y M 2y O 12 In some embodiments, the LLZO particles have a stoichiometric composition of Li 7-3nx M1 x La 3 Zr 2-my M2 y O 12 where M1 is a low atomic mass metal, x is about 0.1 to 0.3, and n can depend on the valence of M1. In some embodiments, the LLZO particles have a stoichiometric composition of Li 7-3nx M1 x La 3 Zr 2-my M 2y O 12 where y is about 0.4 or greater and m may depend on the valence of M2.

[0006] In some embodiments, the LLZO particles can be crystalline. In some embodiments, the crystal structure of the LLZO particles can be a crystalline garnet structure. In some embodiments, the crystalline garnet structure can be a garnet single crystal structure. In some embodiments, the LLZO particles can be amorphous. In some embodiments, the LLZO particles can be a combination of amorphous and crystalline structures.

[0007] Also disclosed herein are embodiments of a solid-state battery, the solid-state battery may include an anode; a cathode; a solid electrolyte; a separator, wherein any of the anode, cathode, or separator includes LLZO particles; the LLZO powder may include LLZO particles; the LLZO particles have a D50 of about 20 nm to about 500 nm, a D10 of D50÷4 or more, and a D90 of D50×4 or less; and the LLZO particles have a sphericity factor of greater than about 0.6. The structure of LLZO particles is either a crystalline garnet structure or an amorphous structure.

[0008] In some embodiments, the anode can include LLZO particles. In some embodiments, the cathode can include LLZO particles. In some embodiments, the separator can include LLZO particles. In some embodiments, the separator can be a composite or ceramic non-composite separator.

[0009] Further disclosed herein are embodiments of a method for producing LLZO powder, the method can include the steps of: preparing an LLZO feedstock of metal salts including lithium, lanthanum, zirconium, tantalum, and a dopant; introducing the LLZO feedstock into a microwave plasma torch, a plasma plume of the microwave plasma torch, and / or an exhaust gas of the microwave plasma torch; and pyrolyzing the LLZO feedstock in the microwave plasma torch, the plasma plume of the microwave plasma torch, and / or an exhaust gas of the microwave plasma torch to form a spheroidized LLZO powder.

[0010] In some embodiments, the LLZO feedstock can be a solid feedstock. In some embodiments, the LLZO feedstock can be a liquid feedstock. In some embodiments, the dopant can be one or any combination of Al, B, Ga, Be, Fe, Zn, Ta, Nb, Tc, Ce, Ti, Sn, Mo, Ru, Hf, Mg, Sc, Mn, Ni, Cu, Co, Ir, Pt, and Pd. In some embodiments, the method can further include sintering the spheroidized LLZO powder. [Brief description of the drawings]

[0011] [Figure 1] An example of LLZO particles produced by solid-gel synthesis is shown.

[0012] [Diagram 2]An example of LLZO particles produced by spray pyrolysis is shown.

[0013] [Diagram 3] 1 shows an embodiment of LLZO nanoparticles produced by a microwave plasma method.

[0014] [Figure 4A] 1 illustrates an example of a microwave plasma processing system. [Figure 4B] 1 illustrates an example of a microwave plasma processing system. [Figure 4C] 1 illustrates an example of a microwave plasma processing system.

[0015] [Diagram 5] 1 illustrates an example embodiment of a method for producing a powder according to the present disclosure.

[0016] [Figure 6] 1 illustrates an embodiment of a microwave plasma torch that can be used in powder production according to an embodiment of the present disclosure.

[0017] [Figure 7A] 1 illustrates an embodiment of a microwave plasma torch that can be used in powder production according to an embodiment of the side feed hopper of the present disclosure. [Figure 7B] 1 illustrates an embodiment of a microwave plasma torch that can be used in powder production according to an embodiment of the side feed hopper of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Disclosed herein are embodiments of improved lithium lanthanum zirconium oxide (LLZO) powders and products, as well as methods, apparatus, and assemblies for utilizing LLZO materials produced by plasma processing. A promising class of ion-conducting ceramics for solid-state battery cells is based on LLZO. These materials have been shown to be highly effective in reducing the thermal stresses of solid-state batteries. -3The present disclosure has a room temperature ionic conductivity of 0.1 S / cm or less and excellent electrochemical stability. The present invention can be incorporated into solid-state batteries, such as as separators, electrodes, anodes, and / or cathodes.

[0019] Current solid-state batteries can be equipped with either conventional non-composite or composite separators. In both non-composite and composite separators, fine-grained, spherical particle morphology and narrow particle size distribution are ideal, and embodiments of the present disclosure can produce such particles.

[0020] In the manufacture of ionic membrane separators, powders can be consolidated into thin films by different methods. In one of these methods, the powders can be mixed with ion-conducting polymers to produce composite membrane separators. In another example, the powders can be consolidated into ribbons by sintering to produce non-composite separators. Both of these separators have the advantage of tight control over particle size, particle size distribution, and high chemical purity, which are advantageously disclosed herein. In ceramic electrolyte non-composite separators, the material can be either amorphous or crystalline. In composite electrolyte separators, the material can be crystalline.

[0021] Conventional LLZO production typically involves producing powders by solid-state or sol-gel synthesis and then milling to size, which is costly in terms of energy and yield, and results in irregularly shaped particles and a large particle size distribution range, as shown in Figure 1.

[0022] Alternatively, companies have used spray pyrolysis, which involves feeding the precursor solution into a high-temperature furnace. However, this method has limited control over the processing temperature and environment. This results in a wide particle size distribution, many phase impurities, and low particle density, as shown in Figure 2, making it unsuitable for use in separator membranes.

[0023] In either case, these characteristics result in poor material packing in the green state, poor interparticle contact forces, low driving forces for sintering due to large grain size, and poor grain coordination with other grains. The green state can be defined as the grains after production but before sintering. Rapid full density sintering of defect-free separators may not occur when LLZO powders are produced by milling and / or spray pyrolysis. Separator membranes produced with LLZO prepared by these methods may have residual porosity and large grain size distribution, which may lead to premature failure.

[0024] The embodiments of the present disclosure relate to LLZO powders with small or narrow particle size, small or narrow particle size distribution, and relatively spherical morphology, which can have advantageous properties for solid-state batteries. Superior LLZO can be produced using plasma treatments, such as microwave plasma processes. LLZO processed using plasma treatments can be spherical particles with tight particle size distributions (e.g., 100-500 nm), desired stoichiometric compositions, and various crystal structures. An embodiment of microwave plasma-treated LLZO can be seen in FIG. 3. As shown in the figure, the processed LLZO can have highly spherical nanoscale material that can be sintered to high density.

[0025] In some embodiments, the particles can exhibit a crystalline structure. In some embodiments, the crystalline structure can be a garnet crystalline structure. In some embodiments, the particles can be amorphous. In some embodiments, the particles can be a combination of crystalline and amorphous. In some embodiments, the particles can have (or generally have) phase purity.

[0026] In some embodiments, the particles can be fully crystalline. In some embodiments, the particles can be 99% (or about 99%) crystalline (and thus 1% amorphous). In embodiments, the particles may be greater than 50%, 60%, 70%, 75%, 80%, 85%, 90%, 95%, or 99% crystalline (or about 50%, about 60%, about 70%, about 75%, about 80%, about 85%, about 90%, about 95%, or about 99% crystalline).

[0027] In some embodiments, the sphericity factor can be greater than 0.3, 0.4, 0.5, 0.6, 0.7, or 0.8 (or greater than about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, or about 0.8). In some embodiments, the sphericity factor can be less than 0.3, 0.4, 0.5, 0.6, 0.7, or 0.8 (or less than about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, or about 0.8).

[0028] In some embodiments, the particle size of the powder can be tunable D50 of 20 nm to 500 nm (or about 20 nm to about 500 nm), 50 nm to 500 nm (or about 50 nm to about 500 nm), 100 nm to 400 nm (or about 100 nm to about 400 nm), or about 150 nm to about 300 nm (or about 150 nm to about 300 nm). In some embodiments, the D50 of the particles can be 200 nm (or about 200 nm). In some embodiments, the D10 can be D50÷4. In some embodiments, the D10 can be D50÷2. In some embodiments, the D90 can be D50×4. In some embodiments, the D90 can be D50×2. For example, if D50 is 200 nm, D50÷2 would be 100 nm, D50÷4 would be 50 nm, D50×4 would be 800 nm, and D50×2 would be 400 nm. D10 can be defined as the diameter at which 10% of the LLZO powder consists of particles with a diameter below this value. D50 can be defined as the diameter at which 50% of the LLZO material consists of particles with a diameter below this value. D90 can be defined as the diameter at which 90% of the LLZO material consists of particles with a diameter below this value.

[0029] In some embodiments, the stoichiometric composition of the powder is represented by the formula Li 7-nxM1 x La 3 Zr 2-my M 2y O 12 where n and m may depend on the valence of M1 and M2. In some embodiments, M1 and M2 may be any element of the periodic table. In some embodiments, M1 is a low atomic mass metal such as Al, B, Ga, Be, Fe, and Zn, and M2 may be Ta, Nb, Tc, Ce, Ti, Sn, Mo, Ru, Hf, Mg, Sc, Mn, Ni, Cu, Co, Ir, Pt, and Pd. In some embodiments, when M1 is a low atomic mass metal such as Al, B, or Ga, the stoichiometric composition is represented by the formula Li 7-3x M1 x La 3 Zr 2 O 12 In some embodiments, when M2 is a pentavalent metal such as Ta or Nb, the stoichiometric composition can be controlled according to the formula Li 7-y La 3 Zr 2-y M2 y O 12 In some embodiments, B is used as a dopant to control the dopant concentration of Li 7-3x BxLa 3 Zr 2 O 12 In some embodiments, the stoichiometric composition of the powder is Li 6.75 La 3 Zr 2.53 O 12 In some embodiments, M1 dopants can be used to produce a garnet crystal structure.

[0030] In some embodiments, the plasma-treated LLZO can have a fine grain size that exhibits a greater driving force for densifying the material during sintering, which facilitates shorter sintering times and lower temperatures compared to conventionally produced LLZO materials. The tight grain size distribution and spherical morphology can allow for a high specific mass deviation that speeds sintering. The short sintering times and low sintering temperatures can lead to the plasma-treated LLZO being suitable for pressureless sintering.

[0031] Furthermore, precise particle size and spherical morphology can reduce the occurrence of stable pores that cannot be sintered. Fewer stable pores can result in improved end quality of the material. Strict particle size distribution also reduces abnormal growth that results in excessively large particles and broad particle size distribution. This can result in controlled grain growth that prevents

[0032] In some embodiments, sintering can be performed to a density of greater than 98.5% with a maximum grain size of 2 μm or less. In some embodiments, the porosity after sintering can be less than 5%, 4%, 3%, 2%, 1%, or 0.5% (or less than about 5%, about 4%, about 3%, about 2%, about 1%, or about 0.5%). In some embodiments, the porosity after sintering can be greater than 5%, 4%, 3%, 2%, 1%, or 0.5% (or greater than about 5%, about 4%, about 3%, about 2%, about 1%, or about 0.5%). In some embodiments, the ionic conductivity of the plasma-treated LLZO after sintering is greater than 10%. -3 S / cm.

[0033] feedstock In some embodiments, the feedstocks used to make the ionically conducting LLZO materials can be metal salts of related elements such as nitrates and acetates of lithium, lanthanum, zirconium, tantalum, and aluminum. These salts can be dissolved and mixed in the correct proportions to obtain the desired stoichiometric composition. In some embodiments, mixtures of metal salts can be used.

[0034] In some embodiments, lanthanum, lithium, and aluminum nitrates are mixed with zirconium acetate to produce the solution feedstock to obtain the desired stoichiometric composition, in some embodiments, lithium hydroxide can be used as opposed to lithium nitrate to increase the lithium concentration in the salt.

[0035] In some embodiments, lithium or lanthanum may volatilize during processing, reducing the metal yield in the final product. The metal salt can be increased to compensate for the volatilized metal.

[0036] In some embodiments, the other feedstock used to produce the ionically conductive LLZO material can be non-lithium-containing ceramic powder particles in the particle size range of 20-1000 nm in a carrier solution that is mixed with a dispersing medium to obtain a dispersion, suspension, slurry, or similar mixture. The carrier solution can be water, alcohol, or other non-polar solvent.

[0037] In some embodiments, lithium carbonate can be partially dissolved in a carrier solution and mixed with stoichiometric ratios of lanthanum oxide, zirconium oxide, and aluminum oxide in a dispersing medium such as water and Triton X to produce a stable suspension. In some embodiments, the dispersion or slurry can contain a combination of ceramic oxide powders mixed with soluble metal salts. Lithium nitrate and lanthanum nitrate can be mixed with aqueous solutions of zirconium oxide and aluminum oxide to produce a slurry.

[0038] Treatment process Precursor production The process can begin by dissolving the desired metal salts of dopants, such as lithium, lanthanum, zirconium, and aluminum, in stoichiometric ratios in a solvent, such as water, or, in the case of a dispersion, by dispersing the powders in a carrier solution. The amount of each salt can be calculated to obtain the desired final stoichiometric composition of the LLZO material to be produced. In some embodiments, Li 7 La 3Zr 3 O 12 In the case of producing LLZO, the amount of lithium salt would be calculated to give 7 moles of lithium, the amount of lanthanum salt would be calculated to give 3 moles of lanthanum, and the amount of zirconium salt would be calculated to give 2 moles of zirconium in the final LLZO product.

[0039] In the case of dopants, the stoichiometry of the formula can be adjusted accordingly. In some embodiments, aluminum replaces lithium in the LLZO structure. Lithium was added to the feed in an amount equivalent to that of aluminum, with the formula Li 7-3x Al x La 3 Zr 2 O 12 where x=0.1-0.3. If 0.25 molar aluminum is desired as the dopant, the lithium concentration is reduced from 7 molar to 6.25 molar to maintain stoichiometry and charge neutrality.

[0040] In some embodiments, lithium or lanthanum may be vaporized during processing which can increase the metal weight in the final product. The metal salt can be increased to compensate for the vaporized metal.

[0041] Plasma treatment The dissolved salt can be thoroughly stirred and then filtered, for example, through a filter membrane with a pore size of 0.05-0.6 μm, to obtain a clean solution free of sediment or insoluble impurities. The resulting solution precursor can be transferred to a tank that feeds into a droplet generator located on top of a microwave plasma torch. Precursor tank embodiments include a syringe or a hopper beaker. From the precursor tank, the feedstock can be fed towards the droplet generator. Some droplet generator embodiments include nebulizers and atomizers. The droplet generator can generate solution precursor droplets that are roughly equivalent to the particle size with a diameter in the range of roughly 5%. The droplets can be fed into a microwave plasma torch, into the plasma plume of the microwave plasma torch, and / or into the exhaust gas of the microwave plasma torch.

[0042] A system overview can be seen in Figures 4A-4C. Figure 4A is a schematic diagram of one example of an implementation of a microwave plasma processing system. The system includes a droplet generator 402. Figure 4B shows a diagram of the droplet generator 402. The droplet generator 402 can be a piezoelectric droplet generator that uses a voltage to actuate a valve that opens and closes to release liquid out of the valve. The droplet generator 402 generates highly controlled droplets 404 of a controlled size. Figure 4C shows a diagram of the droplets 404. The size of the droplets 404 correlates to the final size. The droplets 404 enter a plasma chamber 406. The plasma chamber 406 is coupled to a waveguide 408. The waveguide 408 is coupled to a microwave generator 410 that generates a microwave frequency signal that passes through the waveguide 408. The microwave frequency signal excites a gas in the plasma chamber 406 that generates a plasma. In some embodiments, the plasma 406 can be an axisymmetric plasma. The droplets 404 are fed into a plasma 406 where the droplets dissociate to form particles 412. The droplets 404 may be fed by the plasma, the plasma plume, or the plasma exhaust. The particles 412 are collected in a collection bin 414.

[0043] As each droplet is heated in a plasma hot zone generated by a microwave plasma torch, the solvent can vaporize, the solvent can precipitate, and pyrolysis can occur. Pyrolysis under oxygen plasma can produce oxide compounds consisting of lithium, lanthanum, zirconium, and dopant selections M1 and M2. The plasma gas can be oxygen, or alternatively a blend of three or less gases with a minimum oxygen concentration of 1%. In some embodiments, one of the three or less gases is argon.

[0044] In some embodiments, the droplet generator can be installed on the side of a microwave plasma torch, such as that shown in Figure 7A. The feedstock material can be fed from the side of the microwave plasma torch by the droplet generator. The droplets can be fed into the microwave-generated plasma from either direction.

[0045] Amorphous materials can be produced by decomposing the precursors into oxide materials and then cooling at a rate sufficient to prevent the atoms from reaching a crystalline state. Cooling rates can be achieved by quenching the droplets within 0.05 to 2 seconds of pyrolysis in a high velocity gas stream. The gas flow temperature may range from -150°C to 40°C.

[0046] Alternatively, crystalline materials can be produced if the plasma length and reactor temperature are sufficient to provide particles with the time and temperature required for atoms to diffuse to their thermodynamically preferred crystallographic locations. The plasma length and reactor temperature can be adjusted with parameters such as power, torch diameter, reactor length, gas flow rate, gas flow characteristics, and torch type. In some embodiments, a higher degree of crystallinity can be obtained with a longer plasma length. In some embodiments, a higher degree of crystallinity can be obtained with a higher temperature. In some embodiments, the temperature can be adjusted to be high enough to provide crystallinity and low enough not to melt or vaporize the particles. In some embodiments, the temperature can be between 900°C and 1600°C.

[0047] Spheroidization In some embodiments, the final particles obtained by plasma treatment may be spherical or ellipsoidal, and these terms may be used interchangeably. Advantageously, by using the important specific disclosures associated with each of the various feedstocks disclosed, all of the feedstocks can be transformed into spherical powders.

[0048] Embodiments of the present disclosure are directed to the production of particles that are substantially spherical or ellipsoidal, or significantly spheroidized. In some embodiments, spherical, ellipsoidal, or spheroidized particles refer to particles that have a sphericity greater than a predetermined threshold. The surface area, A, of a sphere having a volume that coincides with the volume V of the particle is calculated using the following formula: s,ideal can be calculated:

number

number

[0049] In some embodiments, the particles can have a sphericity (also referred to herein as a sphericity factor) of 0.5, 0.6, 0.7, 0.75, 0.8, 0.9, 0.91, 0.95, or greater than 0.99 (or about 0.5, about 0.6, about 0.7, about 0.75, about 0.8, about 0.8, about 0.91, about 0.95, or greater than about 0.99). In some embodiments, the particles can have a sphericity of 0.75 or greater or 0.91 or greater (or about 0.75 or greater or about 0.91 or greater). In some embodiments, the particles can have a sphericity of 0.5, 0. 0.6, 0.7, 0.75, 0.8, 0.9, 0.91, 0.95, or less than 0.99 (or less than about 0.5, about 0.6, about 0.7, about 0.75, about 0.8, about 0.8, about 0.91, about 0.95, or about 0.99). In some embodiments, a particle is considered to be spherical, ellipsoidal, or spheroidized if it has a sphericity equal to or greater than any of the foregoing sphericity values, and in some embodiments, a particle is considered to be spherical if its sphericity is about 0.75 or greater, or about 0.91 or greater.

[0050] In some embodiments, the median sphericity of all particles in a given powder can be greater than 0.5, 0.6, 0.7, 0.75, 0.8, 0.9, 0.91, 0.95, or 0.99 (or greater than about 0.5, about 0.6, about 0.7, about 0.75, about 0.8, about 0.8, about 0.91, about 0.95, or about 0.99). In some embodiments, the median sphericity of all particles in a given powder can be less than 0.5, 0.6, 0.7, 0.75, 0.8, 0.9, 0.91, 0.95, or 0.99 (or less than about 0.5, about 0.6, about 0.7, about 0.75, about 0.8, about 0.8, about 0.91, about 0.95, or about 0.99). In some embodiments, a powder is considered to be spheroidized if all or a threshold percentage of the particles measured for a given powder (listed by any of the fractions below) have a median sphericity equal to or greater than any of the aforementioned sphericity values, and in some embodiments, a powder is considered to be spheroidized if all or a threshold percentage of the particles have a median sphericity equal to or greater than about 0.75 or equal to or greater than about 0.91.

[0051] In some embodiments, the fraction of particles in a powder that may be greater than a given sphericity threshold, such as those described above, may be greater than 50%, 60%, 70%, 80%, 90%, 95%, or 99% (or greater than about 50%, about 60%, about 70%, about 80%, about 90%, about 95%, or about 99%). In some embodiments, the fraction of particles in a powder that may be greater than a given sphericity threshold, such as those described above, may be less than 50%, 60%, 70%, 80%, 90%, 95%, or 99% (or less than about 50%, about 60%, about 70%, about 80%, about 90%, about 95%, or about 99%).

[0052] Particle size distribution and sphericity may be determined by any suitable known technique such as SEM, optical microscopy, dynamic light scattering, laser diffraction, manual measurement of dimensions using image analysis software from, for example, about 15-30 measurements per image for at least 3 images of the same material section or sample, and any other technique.

[0053] Microwave Plasma Treatment The above disclosed particles / structures / powders / precursors can be used in several different processing procedures, for example spray / flame pyrolysis, radio frequency plasma treatment, and high temperature spray dryers can all be used.

[0054] In some cases, the feedstock may include a well-mixed slurry containing the constituent solid materials suspended in a liquid carrier medium that can be delivered by a droplet generator. Some embodiments of the droplet generator include a nebulizer and an atomizer. The droplet generator can generate solution precursor droplets having diameters in the range of approximately 1 μm to 200 μm. The droplets can be delivered into a microwave plasma torch, the plasma plume of the microwave plasma torch, the afterglow of the plasma plume, and / or the exhaust gas of the microwave plasma torch. As each droplet is heated in the plasma hot zone generated by the microwave plasma torch, the carrier liquid is removed and the remaining dry components melt to generate molten droplets containing the constituent elements. The plasma gas can be argon, nitrogen, helium, hydrogen, or a mixture thereof.

[0055] In some embodiments, the droplet generator is mounted on the side of a microwave plasma torch. The feed material can be fed from the side of the microwave plasma torch by a droplet generator. The droplets can be fed into the microwave generated plasma from either direction.

[0056] Amorphous materials can be produced after processing the precursors into the desired material and then cooling at a rate sufficient to prevent the atoms from reaching a crystalline state. Cooling rates can be achieved by quenching the material within 0.05 to 2 seconds of processing in a high velocity gas stream. High velocity gas stream temperatures can range from -200°C to 40°C.

[0057] Alternatively, crystalline materials can be produced if the plasma length and reactor temperature are sufficient to provide particles with the time and temperature necessary for atoms to diffuse to their thermodynamically preferred crystallographic positions. Plasma length and reactor temperature can be adjusted with parameters such as power (2-120 kW), torch diameter (0.5-4 inches), reactor length (0.5-30 feet), gas flow rate (1-20 CFM), gas flow characteristics (laminar or turbulent), and torch type (laminar or turbulent). Longer times at the appropriate temperature result in higher crystallinity.

[0058] The process parameters can be optimized to obtain maximum spheroidization, which depends on the powder initial conditions. For each feedstock powder characteristics, the process parameters can be optimized for a specific result. US Patent Application Publication No. 2018 / 0297122, US Patent No. 8,748,785, and US Patent No. 9,932,673 disclose specific process techniques that can be used for the disclosed methods, in particular microwave plasma processing. Thus, US Patent Application Publication No. 2018 / 0297122, US Patent No. 8,748,785, and US Patent No. 9,932,673 are incorporated herein by reference in their entirety, and the description of these techniques should be considered as applicable to the feedstocks described herein.

[0059] One aspect of the disclosure includes a method for spheroidizing metals, metal alloys, or ceramics using microwave-generated plasma. Powder feedstock is entrained in an inert and / or reducing and / or oxidizing gas environment and injected into the microwave plasma environment. Upon injection into the hot plasma, the feedstock is spheroidized and discharged into a chamber filled with an inert gas and introduced into a hermetically sealed drum for storage. The method can be carried out at atmospheric pressure, partial vacuum, or slightly above atmospheric pressure. In alternative embodiments, the method can be carried out in low, medium, or high vacuum environments. The method can be carried out continuously, with the drum being replaced when filled with spheroidized particles.

[0060] The cooling rate of the spheroidized metal, metal alloy, or ceramic can be controlled to strategically influence the microstructure of the powder. By controlling process parameters such as cooling gas flow rate, residence time, cooling gas composition, etc., the microstructure of the metal, metal alloy, or ceramic can be controlled. The exact cooling rate required to form these structures depends in large part on the type and amount of alloying elements in the material.

[0061] In particular, the cooling rate when combined with the consistent and uniform heating capabilities of the microwave plasma plume allows for control over the final microstructure. As a result, the method can be applied to the processing of metals, metal alloys, or ceramic feedstocks.

[0062] Cooling treatment parameters include, but are not limited to, cooling gas flow rate, residence time of the spheroidized particles in the hot zone, and the composition or method of manufacture of the cooling gas. For example, the cooling or quenching rate of the particles can be increased by increasing the flow rate of the cooling gas. The faster the cooling gas flows past the spheroidized particles exiting the plasma, the faster the quenching rate can be increased. The chelating rates are higher, thereby allowing a particular desired microstructure to be fixed.

[0063] The residence time of the particle within the hot zone of the plasma can also be adjusted to provide control over the resulting microstructure; that is, the length of time the particle is exposed to the plasma determines the degree of melting of the particle (i.e., the surface of the particle melted compared to the bulk or center of the particle). As a result, the degree of melting affects the extent of cooling required to solidify, and therefore the cooling process parameters.

[0064] Microstructural changes can be incorporated into the entire particle or only a portion of it, depending on the extent of particle melting. Residence time can be adjusted by adjusting operational variables such as particle injection rate and flow rate (and conditions such as laminar or turbulent flow) within the hot zone. Equipment modifications can also be used to adjust residence time. For example, residence time can be adjusted by changing the cross-sectional area of ​​the hot zone.

[0065] Another cooling process parameter that can be varied or controlled is the composition of the cooling gas. Certain cooling gases are more thermally conductive than others. For example, helium is considered to be a more thermally conductive gas. The more thermally conductive the cooling gas, the faster the spheroidized particles can be cooled / quenched. By controlling the composition of the cooling gas (e.g., controlling the amount or ratio of higher thermal conductivity gas to lower thermal conductivity gas), the cooling rate can be controlled.

[0066] The microstructure of a metal, metal alloy, or ceramic can be determined by the composition of the material and the heating and cooling / quenching of the material. Control of the microstructure of the spheroidized particles is achieved by selecting (or knowing) the composition of the feedstock material, then exposing the feedstock to a plasma that has a uniform temperature profile and controls it as provided by a microwave plasma torch, and then selecting and controlling the cooling parameters. In addition, the phase of the material may depend on the composition of the feedstock material (e.g., purity, composition of alloying elements, etc.) as well as the heat treatment.

[0067] In one exemplary embodiment, an inert gas is continuously purged around the powder metal, metal alloy, or ceramic feed to remove oxygen in the powder feed hopper. The continuously fed powder is then entrained in the inert gas and fed into a microwave-generated plasma for dehydrogenation or maintaining the composition / purity of the spheroidized particles. In one example, the microwave-generated plasma may be generated using a microwave plasma torch as described in U.S. Patent Application Publication No. 2013 / 0270261 and / or U.S. Patent Nos. 8,748,785, 9,023,259, 9,206,085, 9,242,224, and 10,477,665, each of which is incorporated herein by reference in its entirety.

[0068] In some embodiments, the particles are exposed to a uniform temperature profile of 4,000-8,000 K in the microwave generated plasma. In some embodiments, the particles are exposed to a uniform temperature profile of 3,000-8,000 K in the microwave generated plasma. The powder particles are rapidly heated and melted in the plasma torch. In some embodiments, liquid convection creates a H2O flow throughout the molten particles. 2 Accelerate the diffusion of hydrogen (H 2 ) continuously, reducing the time each particle must reside in the process environment compared to solid-state processes. When the particles in the process are entrained in an inert gas such as argon, there is generally minimal particle-to-particle contact, greatly reducing the occurrence of particle agglomeration. Thus, the need for post-processing sieving is greatly reduced or eliminated, and the resulting particle size distribution will be partially the same as the particle size distribution of the input feed material. In an exemplary embodiment, the particle size distribution of the feed material is maintained in the final product.

[0069] Within the plasma, the molten particles are essentially spheroidized by liquid surface tension. Because microwave-generated plasma exhibits a substantially uniform temperature profile, it may be possible to achieve greater than 90% spheroidization of the particles (e.g., 91%, 93%, 95%, 97%, 99%, 100%). After exiting the plasma, the particles are cooled before entering a collection bin. When the collection bin becomes full, it is removed without stopping the process and replaced with an empty bin as necessary.

[0070] 5 is a flow chart illustrating an exemplary method (250) for producing spherical powders according to an embodiment of the present disclosure. In this embodiment, the method (250) begins with the introduction of a feed material to a plasma torch (255). In some embodiments, the plasma torch is a microwave-generated plasma torch or an RF plasma torch. Within the plasma torch, the feed material is exposed to a plasma, melting the material (260), as described above. The molten material is spheroidized (260b) by surface tension forces, as described above. After exiting the plasma, the product cools and solidifies, setting into a spherical shape, and is then collected (265).

[0071] In some embodiments, the environment and / or bottle sealing requirements are carefully controlled; that is, the environment and / or bottle sealing is tailored to the application to prevent contamination or potential oxidation of the powder. In one embodiment, the bottle is under vacuum. In one embodiment, the bottle is hermetically sealed after being filled with the powder produced by the present technique. In one embodiment, the bottle is backfilled with an inert gas, e.g., argon. Due to the continuity of the process, once the bottle is filled, it is removed without stopping the plasma process and replaced with an empty bottle, if necessary.

[0072] Methods and processes according to the present disclosure can be used to produce powders, such as spherical powders.

[0073] In some embodiments, the processes described herein, such as microwave plasma treatments, can be controlled to prevent and / or minimize the escape of certain elements from the feedstock during melting, thereby maintaining a desired composition / microstructure.

[0074] 6 shows an exemplary microwave plasma torch that can be used in powder production according to embodiments of the present disclosure. As described above, feed material 9, 10 can be introduced into microwave plasma torch 3, which sustains microwave generated plasma 11. In one example embodiment, entrainment gas flow and sheath flow (down arrows) can be injected through inlet 5 to create flow conditions within the plasma torch prior to ignition of plasma 11 by microwave irradiation source 1.

[0075] In some embodiments, the entrainment and sheath flows are both axisymmetric and laminar, while in other embodiments the gas flows are swirling. Feed materials 9 are introduced axially into the microwave plasma torch, where they are entrained in a gas flow that directs the materials in the direction of the plasma. As mentioned above, the gas flow can be of the noble gas column of the periodic table, such as helium, neon, argon, and others. In the microwave-generated plasma, the feed materials are melted to spheroidize the materials. Inlet 5 can be used to introduce a process gas to entrain and accelerate particles 9, 10 along axis 12 in the direction of plasma 11. First, the particles 9 are accelerated by entrainment with a central laminar gas flow (upper set of arrows) created through an annular gap in the plasma torch. A second laminar flow (lower set of arrows) is created through a second annular gap to provide a laminar flow sheathed against the inner wall of the dielectric torch 3 to protect it from melting due to thermal radiation from the plasma 11. In an exemplary embodiment, the laminar gas flow is a laminar gas flow (upper set of arrows) ... The flow directs the particles 9,10 towards the plasma 11 along a path as close as possible to the axis 12, exposing them to a substantially uniform temperature within the plasma.

[0076] In some embodiments, suitable flow conditions are provided to prevent the particles 10 from reaching the inner walls of the plasma torch 3 where plasma deposition may occur. The particles 9, 10 are guided by gas flow towards the microwave plasma 11 and are uniformly heat treated, respectively. Various parameters of the microwave generated plasma as well as particle parameters may be adjusted to obtain the desired results. These parameters may include microwave power, feed size, feed insertion rate, gas flow rate, plasma temperature, residence time and cooling rate. In some embodiments, the cooling or quenching rate is determined by the amount of the particles 10 as they exit the plasma 11. +3 °C / sec or greater. As noted above, in this particular embodiment, the gas flow is laminar; however, in alternative embodiments, vortices or turbulence may be used to direct the feed material toward the plasma.

[0077] 7A-B illustrate an exemplary microwave plasma torch that includes a side-feed hopper rather than the top-feed hopper shown in the embodiment of FIG. 6, thus allowing downstream feeding. Thus, in this practice, feedstock is injected after the microwave plasma torch energizing electrode for processing in the "plume" or "exhaust gas" of the microwave plasma torch. Thus, the plasma of the microwave plasma torch is engaged at the exit end of the plasma torch, allowing downstream feeding of the feedstock as opposed to the top-feed (or downstream feeding) described with respect to FIG. 6. This downstream feeding can advantageously extend the life of the torch since the hot zone is protected indefinitely from material deposition on the walls of the hot zone liner. Furthermore, this allows for precise targeting of temperature levels and residence times to engage the plasma plume downstream at a temperature suitable for optimal melting of the powder. For example, the length of the plume can be scaled using the microwave powder, gas flow, and pressure in the quench vessel containing the plasma plume.

[0078] In general, the downstream spheroidization method can utilize two main hardware configurations to establish a stable plasma plume: an annular torch, such as described in US Patent Application Publication No. 2018 / 0297122, or a vortex torch, as described in US Patent No. 8,748,785 (B2) and US Patent No. 9,932,673 (B2). Both Figures 7A and 7B show an embodiment of the method that can be practiced with either an annular torch or a vortex torch. A feeding system that is closely coupled with the plasma plume at the exit of the plasma torch is used to feed the powder axially symmetrically to maintain process uniformity.

[0079] Other feed configurations may include one or several individual feed nozzles surrounding the plasma plume. Feed powder may enter the plasma at a point from any direction and may be fed to a point within the plasma from any direction 360° around the plasma. Feed powder may enter the plasma for a residence time estimated to be sufficient to melt particles at a particular location along the length of the plasma plume where a particular temperature is measured. The molten particles exit the plasma into a sealed chamber where they are quenched and then collected.

[0080] A feed material 314 can be introduced into the microwave plasma torch 302. A hopper 306 can be used to store the feed material 314 before delivering it to the microwave plasma torch 302, the plume, or the exhaust gas. The feed material 314 can be injected at any angle to the length of the plasma torch 302, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, or 55 degrees. In some embodiments, the feed material can be injected at an angle greater than ... , the feedstock may be injected at an angle of less than 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, or 55 degrees. In an alternative embodiment, the feedstock may be injected along the longitudinal axis of the plasma torch.

[0081] Microwave radiation can be directed to the plasma torch through a waveguide 304. A feed material 314 is fed into the plasma chamber 310 and contacts the plasma generated by the plasma torch 302. When contacted with the plasma, plasma plume, or plasma exhaust gases, the feed material melts. While still in the plasma chamber 310, the feed material 314 cools and solidifies before being collected in the vessel 312. Alternatively, the feed material 314 can exit the plasma chamber 310 while still in the molten phase and cool and solidify outside of the plasma chamber. In some embodiments, a quenching chamber may be used, and positive pressure may or may not be used. Although described separately from FIG. 6, it is understood that the embodiment of FIGS. 7A-7B uses similar diagrams and conditions as the embodiment of FIG. 6.

[0082] In some embodiments, the practice of the downstream injection method may use downstream vortex, extended spheroidization, or quenching. Downstream vortex represents an additional vortex component that can be induced downstream from the plasma torch to keep the powder from the tube wall. Extended spheroidization represents an extended plasma chamber that gives the powder a longer residence time. In some embodiments, it may not use downstream vortex, extended spheroidization, or quenching. In some embodiments, it may use one of downstream vortex, extended spheroidization, or quenching. In some embodiments, it may use two of downstream vortex, extended spheroidization, or quenching.

[0083] Powder injection from below may result in shortening or removal of the plasma tube in the microwave region. If the coating is too tough, the microwave energy is shielded from entering the plasma hot zone, reducing the plasma coupling. Sometimes the plasma may even quench and become unstable. A reduction in plasma intensity means a reduction in the powder spheroidization level. Thus, with the feedstock supply below the microwave region and the engagement of the plasma plume at the exit of the plasma torch, the microwave powder to plasma coupling, except for the coating in this region, remains constant throughout the process, allowing sufficient spheroidization.

[0084] Advantageously, therefore, the downstream approach may allow for a process that runs for a longer period of time as coating issues are reduced. Additionally, the downstream approach allows for the ability to inject more powder as coating minimization is not required.

[0085] From the foregoing description, it will be appreciated that the LLZO powder and manufacturing method of the present invention have been disclosed. Although certain components, techniques and embodiments have been described in some detail, it is apparent that many changes can be made in the specific designs, configurations and methods described herein without departing from the spirit and scope of the present disclosure.

[0086] Certain features described in this disclosure in the context of separate practices may also be combined in a single practice. Conversely, various features described in the context of a single practice may also be combined in multiple practices separately or in any suitable subcombination. Furthermore, although features are described above as acting in a particular combination, one or more features from a claimed combination may, in some cases, be cut out of the combination, and the combination may be claimed as any subcombination or a variation of any subcombination.

[0087] Additionally, the methods may be illustrated in the figures or described herein in a particular order. However, such methods need not be performed in the particular order or sequential order shown, nor all methods need to be performed, to achieve desirable results. Other methods not shown or described can be incorporated into the example methods and processes. For example, one or more additional methods can be performed before, after, simultaneously with, or between any of the methods described. Additionally, methods may be rearranged or sequenced in other practices. Furthermore, it should be understood that the separation of various system components in the above practices does not require such separation in all practices, and it should be understood that, in general, the components and systems described can be integrated together in a single product or packaged in multiple products. Additionally, other practices are within the scope of this disclosure.

[0088] Conditional terms such as "can," "could," "might," or "may" are generally intended to convey that particular embodiments include or do not include particular features, elements, and / or steps, unless otherwise specified or understood otherwise by the context when used. Thus, such conditional terms generally do not imply that features, elements, and / or steps are in any way required for one or more embodiments.

[0089] Conjunctions such as the phrase "at least one of X, Y, and Z," unless otherwise specified, are generally understood to have other meanings in the context when used to convey that an item, term, etc. can be either X, Y, or Z. Thus, such conjunctive words generally do not imply that a particular embodiment requires the presence of at least one of X, at least one of Y, and at least one of Z.

[0090] As used herein, language of degree used herein, such as the terms "approximately", "about", "generally", and "substantially", refers to a value, amount, or index close to a specified value, amount, or index that still performs a desired function or obtains a desired result. For example, the terms "approximately", "about", "generally", and "substantially" can refer to an amount that is 10% or less, 5% or less, 1% or less, 0.1% or less, and 0.01% or less of a specified amount. When a specified amount is 0 (e.g., none, not having), the range can be a specific range, not within a specific % of a value. For example, within 10% or less by weight / volume, within 5% or less by weight / volume, within 1% or less by weight / volume, within 0.1% or less by weight / volume, and within 0.01% or less by weight / volume of a specified amount.

[0091] Any particular feature, aspect, method, characteristic, feature, quality, property, element, or the like disclosed herein in connection with the various embodiments can be used in all other embodiments described herein. In addition, it will be recognized that any method described herein may be performed using any device suitable for carrying out the steps described.

[0092] While certain embodiments and variations thereof have been described in detail, other modifications and methods of using these will be apparent to those skilled in the art. It should therefore be understood that various applications, modifications, materials, and substitutions can be made from the specifics herein and equivalents that do not depart from the scope of the disclosure or claims of the present invention.

Claims

1. 1. A lithium lanthanum zirconium oxide (LLZO) powder comprising: comprising LLZO particles; The LLZO particles are produced by plasma treatment; the LLZO particles have a D50 of about 20 nm to about 500 nm, a D10 of D50÷4 or more, and a D90 of D50×4 or less; the LLZO particles have a sphericity factor of greater than about 0.6; The structure of the LLZO particles is a crystalline garnet structure and / or an amorphous structure. LLZO powder.

2. 2. The LLZO powder of claim 1, wherein the D10 is approximately equal to D50 divided by 2.

3. The LLZO powder according to any one of claims 1 to 2, wherein the D90 is approximately equal to D50 x 2.

4. The LLZO powder of any one of claims 1 to 3, wherein the LLZO particles have a D50 of about 50 nm to about 500 nm.

5. The LLZO powder of any one of claims 1 to 3, wherein the D50 is from about 100 nm to about 400 nm.

6. The LLZO powder of any one of claims 1 to 3, wherein the D50 is from about 150 nm to about 300 nm.

7. The LLZO particles are 7-3x M1 x La 3 Zr 2 O 12 7. The LLZO powder of claim 1, having a stoichiometric composition of M1 = M2 + M3, M4 + M5, M6 + M7, M8 + M9, M10 + M11, M12 + M13, M14 + M15, M16 + M17, M18 + M19, M19 + M20, M11 + M21, M12 + M14, M15 + M22, M16 + M17, M17 + M23, M18 + M24, M19 + M25, M19 + M26, M19 + M27, M18 + M28, M19 + M29, M21 + M30, M22 + M31, M22 + M32, M13 + M42, M23 + M14, M24 + M15, M25 + M32, M16 + M17, M22 + M1

8. The LLZO particles are 7-y La 3 Zr 2-y M2 y O 12 7. The LLZO powder of claim 1, having a stoichiometric composition of M2=Ta or Nb, and y=0.4 or more.

9. 1. A solid-state battery comprising: an anode; A cathode; A solid electrolyte; A separator; With Either the anode, the cathode or the separator comprises LLZO particles; The LLZO particles are produced by plasma treatment; the LLZO particles have a D50 of about 20 nm to about 500 nm, a D10 of D50÷4 or more, and a D90 of D50×4 or less; the LLZO particles have a sphericity factor of greater than about 0.6; The structure of the LLZO particles is a crystalline garnet structure. Solid-state battery.

10. 10. The solid-state battery of claim 9, wherein the separator comprises the LLZO particles.

11. 11. The solid state battery of claim 10, wherein the separator is a composite or a ceramic non-composite separator.

12. The LLZO particles are 7-3x M1 x La 3 Zr 2 O 12 7. The LLZO powder of claim 1, having a stoichiometric composition of M1 = Al, where M1 is Al, and x is about 0.1-0.

3.

13. The LLZO particles are 7-3x M1 x La 3 Zr 2 O 12 7. The LLZO powder of claim 1, having a stoichiometric composition of: M1 is B, and x is about 0.1 to 0.3.

Citation Information

Patent Citations

  • Garnet-type ion conductive oxide and method for producing oxide electrolyte sintered body

    JP2019055898A